New magnet design for fast-field-cycling nuclear magnetic resonance - Kruber, Stephan (2013)
A new magnet design for fast-field-cycling nuclear magnetic resonance is described. A topic of interest is the compensation of the magnetic field homogeneity during the generation of the pulsed magnetic field. In contrast with previous solutions, the magnet system here discussed can be electronically controlled. In Kelvin-type magnets used today, the homogeneity of the field is set-up through a current density distribution along the air-cored cylinders that compose the magnet coil. A common feature of this type of magnets is that the magnetic field value and its homogeneity are affected by thermo-mechanical stress during the strong current pulses applied to the coil. In the new design here presented, the problem can be circumvented through a multicoil arrangement driven by individual current sources, allowing an automatic correction of the magnetic field drift and the homogeneity.